Wits Face Database - Bacci, Nicholas; Davimes, Joshua; Steyn, Maryna; Briers, Nanette (My University, 2020)
The human face is important in social, cultural and recognition contexts. Many research fields make use of faces to understand human interaction and identify individuals. Studies relying on facial image data often make use of ad hoc datasets specifically created for those studies as there is a dearth of large scale controlled and matching facial image databases. Actualistic (taken in a real life, natural setting) and standardised databases of facial images can be of extreme value to many research areas, such as facial identification and recognition. While multiple face databases are available, the majority, if not all, are developed in order to address very specific questions and hypotheses with limited standardisation, severely limiting their potential applicability. The Wits Face Database was developed as a generic, yet actualistic dataset of facial images obtained from consenting young adult South African male individuals. This database consists of high resolution standardised facial photographs (3264 x 4080 pixels) and corresponding closed-circuit television (CCTV) recordings of male South Africans under different camera conditions. A total of 6220 standardised (clothing and background controlled) and natural (visible clothing and out of focus background) facial photographs of 622 matching individuals in five different views are included. Corresponding CCTV footage of 334 of these individuals is also included. Across both the CCTV recordings and the photographs, the faces were captured in five different views: anterior, left 45-degree, left lateral, right 45-degree, and right lateral. The CCTV recordings were grouped under the following actualistic conditions: a standard internet protocol (IP) CCTV set-up, a low-resolution analogue CCTV set-up, an eye-level IP CCTV system, and the standard IP CCTV set-up with the addition of sunglasses and caps for target individuals. A detailed description of the composition and acquisition process of the database will be made available in a database descriptor publication format. The database is available strictly for non-commercial scientific research following approval of a formal application, assessed by the School of Anatomical Sciences’ Collections Committee within the University of the Witwatersrand.
WFD
Keywords: CCTV; facial photographs; facial identification; facial comparison; morphological analysis; facial recognition.; Face -- Anatomy and Histology; Videorecording; Image analysis; Photo comparison; Face The anterior portion of the head that includes the skin, muscles, and structures of the forehead, eyes, nose, mouth, cheeks, and jaw.; MeSH Unique ID: D005145; Photography; Image Processing